Multiobjective Optimization Design for Structural Parameters of TBM Disc Cutter Rings Based on FAHP and SAMPGA. (12th September 2019) - Lin, Laikuang; Xia, Yimin; Wu, Dun
Abstract : As a key component of tunnel boring machines (TBMs), the disc cutter ring and its structural parameters are closely related to the TBM tunneling quality. Literature review shows that investigations on optimization design methods for cutter ring structure are seriously insufficient. Therefore, in this paper, a multiobjective optimization design model of structural parameters for disc cutter rings is developed based on the complex geological conditions and the corresponding cutter ring structure design requirements. The rock breaking capability, energy consumption, load-bearing capability, wear life, and wear uniformity of disc cutter are selected as the objectives, and the geometric structure of cutter rings, ultimate load-bearing capability, and cutterhead drive performance are determined as constraints. According to the characteristics of this model, a self-adaptive multipopulation genetic algorithm (SAMPGA) is utilized to solve the optimization problem, and the Fuzzy analytical hierarchy process (FAHP) is employed to calculate weight coefficients for multiple objectives. Finally, the applicability of the proposed method is demonstrated through a case study in a TBM project. The results indicated that the rock breaking performance and service life of the disc cutter are improved after optimization by using the proposed method. The utilization of SAMPGA effectively solves the premature local convergence problems during optimization. The geological adaptability should be considered in the cutter ring structure design, which can be realized by using the proposed method based on the suitable weight coefficients.